Clinical efficacy and safety of ultrasound-assisted thrombolysis vs. standard catheter-directed thrombolysis in patients with acute pulmonary embolism: A study level meta-analysis of clinical trials - Sun, Bing; Yang, Jing Xiao; Wang, Zi Kuan; Zhou, Hai Jia; Chu, Yi; Li, Yan; Chen, Rui Rui (Frontiers in Cardiovascular Medicine, 2022)
Abstract: AIM To compare the clinical efficacy of ultrasound-assisted thrombolysis (USAT) vs. standard catheter-directed thrombolysis (SCDT) in patients with acute pulmonary embolism (aPE). METHODS This study analyzed the clinical outcomes of patients with non-low-risk aPE who received USAT or SCDT. The primary outcomes were all-cause death, total bleeding, and major bleeding. Secondary outcomes included pulmonary thrombotic load score (Miller), improvement in right ventricular–to–left ventricular ratio (RV/LV), dose and duration of the thrombolytic drug tissue plasminogen activator (tPA), length of stay (LOS) in the ICU, and total LOS in the hospital. RESULTS A total of 7 articles and 451 patients were included in this study. 241 patients were in the USAT group and 210 patients were in the SCDT group. There were no significant differences in all-cause mortality, total bleeding, and major bleeding between the two groups. Miller scores for pulmonary thrombus also showed no difference between the two groups, but pulmonary artery systolic pressure (PASP) was lower in the SCDT group after-treatment. The reduction of RV/LV from baseline was more pronounced in the SCDT group than in the USAT group (OR:-0.14, 95%CI: -0.20-0.07, P＜0.0001, I2=0%). Total dose of tPA and duration of infusion in the USAT group were lower than those in the SCDT group, but there was no significant statistical difference. LOS in the ICU was similar between the two groups, while LOS in the hospital was lower in the SCDT group. CONCLUSION This study did not detect any differences in all-cause mortality, total bleeding, and major bleeding between non-low-risk aPE patients treated with USAT or SCDT. Improvement in right ventricular function was better in the SCDT group, and hospital LOS was lower in the SCDT group.